Effect of Socio-Demographic Factor and Democratic Leadership on Village Midwife Performance in IUD Contraceptive Service in Jombang District, East Java - Ratna Dewi Permatasari; Uki Retno Budihastuti; Didik Tamtomo (Journal of Health Policy and Management, 2017)
Background: The threat of population explosion in Indonesia is real. Long-term contraception program is an alternative strategy for controlling population growth rate. The slowering achievement of IUD contraceptive target for the last two years has become a central concern at the District Health Office Jombang, East Java. Sub-optimal quality of IUD contraceptive service, high drop-out rate, high unmet-need, and unsystematic family planning reporting and recording, are assumed to be the causes of the under-achievement. This study aimed to examine the effect of socio-demographic factor and democratic leadership on village midwife performance in IUD contraceptive service in Jombang District, East Java.Subjects and Method: This was an analytic observational study with cross-sectional design. It was conducted in 12 community health centers in Jombang District, East Java, from March to May 2017. A sample of 120 women of reproductive age was selected for this study by simple random sampling. The dependent variable was village midwife performance. The independent variables were knowledge, self-efficacy, compensation, democratic leadership, and work motivation. The data were collected by a pre-tested questionnaire, and were analyzed by path analysis model.Results: Midwife performance was positively affected by higher education (b=5.19; SE=0.53; p<0.001), stronger work motivation (b=0.48; SE=0.07; p<0.001), better knowledge (b=0.21; SE=0.08; p=0.006), stronger self-efficacy (b=0.18; SE=0.08; p=0.023), and democratic leadership (b=0.14; SE=0.05; p=0.008). Self-efficacy was affected by education (b=1.16; SE=0.62; p=0.063), knowledge (b=0.35; SE=0.08; p<0.001), democratic leadership (b=0.23; SE=0.04; p<0.001). Work motivation was affected by compensation (b=0.65; SE=0.16; p<0.001), democratic leadership (b=0.31; SE=0.07; p<0.001), knowledge (b=0.29; SE=0.09; p<0.001), and self-efficacy (b=0.17; SE=0.09; p=0.058).Conclusion: Midwife performance was positively affected by education, work motivation, education, self efficacy, and democratic leadership.Keywords: midwife performance, socio-demographic factor, democratic leadership, IUD contra-ceptive, family planning.Correspondence: Ratna Dewi Permatasari. Masters Program in Public Heath, Sebelas Maret University, Surakarta. Email: wahib.rifai81@gmail.com. Mobile: +6281334059159.Journal of Health Policy and Management (2017), 2(1): 16-27https://doi.org/10.26911/thejhpm.2017.02.01.02